2011
DOI: 10.1051/0004-6361/201015188
|View full text |Cite
|
Sign up to set email alerts
|

Probing tiny convective cores with the acoustic modes of lowest degree

Abstract: Solar-like oscillations are expected to be excited in stars of up to about 1.6 solar masses. Most of these stars will have convective cores during their main-sequence evolution. At the edges of these convective cores, there is a rapid variation in the sound speed, which influences the frequencies of acoustic oscillations. In this paper we build on earlier work to investigate the impact that these rapid structural variations have on different p-mode frequency combinations, involving modes of low degree. In part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…Cunha & Metcalfe (2007) derived a diagnostic applicable to this case and showed that it provided a measure of stellar age. This and similar diagnostic quantities were further analysed by Cunha & Brandão (2011). A similar analysis was carried out by Silva Aguirre et al (2011), demonstrating the potential of such diagnostics to constrain the size of the convective core, including the effects of semiconvection which remain a serious uncertainty in the modelling of stellar evolution.…”
Section: Analysis Of Acoustic Glitchesmentioning
confidence: 61%
“…Cunha & Metcalfe (2007) derived a diagnostic applicable to this case and showed that it provided a measure of stellar age. This and similar diagnostic quantities were further analysed by Cunha & Brandão (2011). A similar analysis was carried out by Silva Aguirre et al (2011), demonstrating the potential of such diagnostics to constrain the size of the convective core, including the effects of semiconvection which remain a serious uncertainty in the modelling of stellar evolution.…”
Section: Analysis Of Acoustic Glitchesmentioning
confidence: 61%
“…In their work, Cunha & Metcalfe (2007) find that the sharp discontinuity formed at the edge of the convective core has a direct impact on the slope of their proposed quantity when plotted against frequency, showing that the absolute value of the slope increases as a function of the size of the chemical discontinuity (and therefore with decreasing amount of central hydrogen content). Since observing l = 3 modes is very challenging owing to severe amplitude reduction, Cunha & Brandão (2011) extended this study by using the small frequency separations defined in Eqs. (12) and (13) and analyzing the changes in the slope, reaching the same conclusions as Cunha & Metcalfe (2007).…”
Section: Discussionmentioning
confidence: 99%
“…As anticipated from the work of Cunha & Brandão (2011), there is a strong dependence of |S {∆ν dr 0213 }| on A δ . Nevertheless, that relation deviates from linear and shows significant dispersion, particularly for larger values of A δ .…”
Section: Relation Between |S {I}| and A δmentioning
confidence: 56%
“…In the case of stars with a convective core we expect that the frequency derivatives of the diagnostic tools taken at their maximum absolute value are a measure of A δ (Cunha & Brandão, 2011). We introduce here a new quantity S {i}, which we shall name 'slope', which is a measure of the frequency derivative of a diagnostic tool 'i', at its maximum absolute value.…”
Section: Slopesmentioning
confidence: 99%